HM4All: A vital signs monitoring system based in spatially distributed ZigBee networks - Fernández-López, Helena (2010)
Low power consumption and small footprint make ZigBee based devices well suited for personal healthcare applications, being a promising alternative to general care patient monitoring. However, their use in a healthcare facility to monitor several mobile patients poses several difficulties, mainly because this protocol was primarily designed to operate in low data rate scenarios. This paper introduces HM4All, a remote vital signs monitoring system, and presents a prototype system being deployed in a hospital internment floor. Its architecture, original network topology, software applications and wireless sensors are described.